Unilateral nephrectomy diminishes ischemic acute kidney injury through enhanced perfusion and reduced pro-inflammatory and pro-fibrotic responses. - Casper Kierulf-Lassen; Per Mose Nielsen; Haiyun Qi; Mads Damgaard; Christoffer Laustsen; Michael Pedersen; Søren Krag; Henrik Birn; Rikke Nørregaard; Bente Jespersen (PLoS ONE, 2017)
While unilateral nephrectomy (UNx) is suggested to protect against ischemia-reperfusion injury (IRI) in the remaining kidney, the mechanisms underlying this protection remain to be elucidated. In this study, functional MRI was employed in a renal IRI rat model to reveal global and regional changes in renal filtration, perfusion, oxygenation and sodium handling, and microarray and pathway analyses were conducted to identify protective molecular mechanisms. Wistar rats were randomized to either UNx or sham UNx immediately prior to 37 minutes of unilateral renal artery clamping or sham operation under sevoflurane anesthesia. MRI was performed 24 hours after reperfusion. Blood and renal tissue were harvested. RNA was isolated for microarray analysis and QPCR validation of gene expression results. The perfusion (T1 value) was significantly enhanced in the medulla of the post-ischemic kidney following UNx. UNx decreased the expression of fibrogenic genes, i.a. Col1a1, Fn1 and Tgfb1 in the post-ischemic kidney. This was associated with a marked decrease in markers of activated myofibroblasts (Acta2/α-Sma and Cdh11) and macrophages (Ccr2). This was most likely facilitated by down-regulation of Pdgfra, thus inhibiting pericyte-myofibroblast differentiation, chemokine production (Ccl2/Mcp1) and macrophage infiltration. UNx reduced ischemic histopathologic injury. UNx may exert renoprotective effects against IRI through increased perfusion in the renal medulla and alleviation of the acute pro-inflammatory and pro-fibrotic responses possibly through decreased myofibroblast activation. The identified pathways involved may serve as potential therapeutic targets and should be taken into account in experimental models of IRI.